The Deubiquitinase USP39 Promotes ESCC Tumorigenesis Through Pre-mRNA Splicing of the mTORC2 Component Rictor - Zhao, Yuan; Geng, Huiwu; Liu, Gang; Ji, Qiang; Cheng, Xiaomin; Li, Xinying; Liu, Wei; Thorne, Rick F.; Zhang, Renquan; Liu, Xiaoying (Frontiers in Oncology, 2021)
Spliceosomes are large RNA-protein molecular complexes which mediate splicing of pre-mRNA in eukaryotic cells. Their function is frequently altered in cancer, providing opportunities for novel therapeutic approaches. The ubiquitin specific protease 39 (USP39) is a highly conserved deubiquitylation family member that plays an essential role in pre-mRNA splicing where it serves to assemble the mature spliceosome complex. Previous studies have reported that USP39 acts in an oncogenic manner where it contributes to cancer progression and predicts poor prognosis in various human tumor types. Here we report that USP39 is differentially upregulated in human esophageal squamous cell carcinoma (ESCC) and its expression is significantly associated with clinicopathological characteristics including differentiation status and TNM stage. We found the USP39 upregulation was maintained in ESCC cell lines where it functioned to promote cancer cell growth in vitro and in xenografts. RNA-seq analyses identified that mTOR pathway activation was affected by shRNA-mediated silencing of USP39. Subsequent biochemical analyses demonstrated that USP39 regulates the activity of mTORC2 by selectively enhancing the splicing and maturation of Rictor mRNA, although not other key mTORC components. Together, our report proposes USP39 as a biomarker and oncogenic factor in ESCC, with a potential for targeting the USP39/mTOR2/Rictor axis as a therapeutic strategy. Furthermore, our study adds ESCC to the list of cancers where USP39 contributes to tumorigenesis and progression.